2010
DOI: 10.1007/s00701-010-0693-7
|View full text |Cite
|
Sign up to set email alerts
|

Angiographic and clinical outcomes of stent-alone treatment for spontaneous vertebrobasilar dissecting aneurysm

Abstract: The SAT could be a feasible alternative for the treatment of VBD. The overlapping technique was significantly associated with good angiographic outcome. We expect that technological development of the intracranial stent will allow better procedural outcomes of SAT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
20
0
2

Year Published

2011
2011
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 39 publications
4
20
0
2
Order By: Relevance
“…[7][8][9] Higher rates of longterm angiographic occlusion with multiple overlapping stents compared with single-stent treatment have been demonstrated in multiple series. [10][11][12] Our study found similar rates of good long-term neurologic outcome between patients treated with reconstructive and deconstructive techniques but higher rates of perioperative morbidity among patients treated with deconstructive techniques. Patients treated with deconstructive techniques are at a higher risk of neurologic complications secondary to ischemia resulting from sacrifice of the parent vessel.…”
Section: Discussionsupporting
confidence: 63%
“…[7][8][9] Higher rates of longterm angiographic occlusion with multiple overlapping stents compared with single-stent treatment have been demonstrated in multiple series. [10][11][12] Our study found similar rates of good long-term neurologic outcome between patients treated with reconstructive and deconstructive techniques but higher rates of perioperative morbidity among patients treated with deconstructive techniques. Patients treated with deconstructive techniques are at a higher risk of neurologic complications secondary to ischemia resulting from sacrifice of the parent vessel.…”
Section: Discussionsupporting
confidence: 63%
“…Successful treatment has been reported as a result of the placement of a stent or other flow-diverting devices [18][19][20][21][22][23]. Although preservation of the parent artery is ideal, the durability of the perforating artery or the anterior spinal artery is not clear.…”
Section: Complications and Follow-upmentioning
confidence: 99%
“…Even though conservative treatment approach including anticoagulation and controlling blood pressure is preferred by some authorities, cases with progressive symptoms resistant to medical therapies, or when anticoagulant treatment is contraindicated or which the dissections require surgical or endovascular treatment [2,3].…”
Section: Discussionmentioning
confidence: 99%
“…The overall incidence of basilar artery dissection is approximately 1-1.5 in 100,000 [2,3]. Little is known about clinical course and prognosis.…”
Section: Introductionmentioning
confidence: 99%